Advection of Mesozooplankton Into the Northern Svalbard Shelf Region - Wassmann, Paul; Slagstad, Dag; Ellingsen, Ingrid (Frontiers in Marine Science, 2019)
The northern Svalbard shelf region is part of the Atlantic advective contiguous domain along which nutrients, phyto- and mesozooplankton are advected with Atlantic Water from the Norwegian Sea along the Norwegian shelf break and into the Arctic Ocean. By applying the SINMOD model, we investigated how much mesozooplankton may be advected into the northern Svalbard shelf region. We also compared this supply with the local mesozooplankton production. To achieve this, we selected a box north of Svalbard and calculated the in- and outflux of Atlantic Calanus finmarchicus and Arctic Calanus glacialis. The average biomass inside the box ranged between 0.5 and 3.0 g C month–2 in March and August, respectively. Annually, 18.8 g C month–2 of advected (and locally produced) mesozooplankton would be available for predators inside the box before it is advected out. The advection of mesozooplankton reached 12 times more than the average biomass within the box. The model projects significance variability in mesozooplankton advection which may be explained by the hitherto non-quantified recirculation in the northern Fram Strait and differences in the geographic origin of the mesozooplankton source population. The results imply that grazing upon mesozooplankton in the Atlantic advective contiguous domain north of Svalbard is greatly advantageous for pelagic predators. It could represent an important food source for fish, birds, and whales. It is suggested that mesozooplankton encountered on the shelf north of Svalbard may derive from populations along the North Norwegian shelf break, in some years as far south as the Lofoten/Vesterålen region. This illustrates the extent and significance of the Atlantic advective contiguous domain for the European shelf of the Arctic Ocean which apparently depends on significant food supply through expatriates. Primary production on the shelf is lower than C consumption and thus the European shelf of the AO is presumably net-heterotrophic.